2005
DOI: 10.1590/s1516-35982005000600035
|View full text |Cite
|
Sign up to set email alerts
|

Casca de algodão em substituição parcial à silagem de capim-elefante para novilhos. 1. Consumo, degradabilidade e digestibilidade total e parcial

Abstract: RESUMO -Quatro novilhos holandeses fistulados no rúmen, com peso médio de 259 kg, foram distribuídos em um quadrado latino 4 x 4 para se avaliar o efeito dos níveis de casca de algodão na dieta de novilhos sobre o consumo e as digestibilidades totais, ruminais e intestinais de matéria seca (MS), matéria orgânica (MO), extrato etéreo (EE), proteína bruta (PB), fibra em detergente neutro corrigida para cinzas e proteína (FDNcp) e carboidratos não-fibrosos corrigidos (CNFcp) e o consumo de nutrientes digestíveis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
(18 reference statements)
2
5
0
6
Order By: Relevance
“…Regarding the dietary volume effect of CSB, a by-product that presents a large amount of cottonseed hulls, the data from this study are partly consistent with the studies of Chizzotti et al (2005), who observed that cottonseed hulls increased the DM intake without changing the weight gain. Moore, Poorem, and Swingle (1990) found that animals that consumed cottonseed hulls instead of alfalfa hay had greater homogeneity of the diet in the rumen and ruminal escape probably was greater and therefore DM intake was stimulated.…”
Section: Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the dietary volume effect of CSB, a by-product that presents a large amount of cottonseed hulls, the data from this study are partly consistent with the studies of Chizzotti et al (2005), who observed that cottonseed hulls increased the DM intake without changing the weight gain. Moore, Poorem, and Swingle (1990) found that animals that consumed cottonseed hulls instead of alfalfa hay had greater homogeneity of the diet in the rumen and ruminal escape probably was greater and therefore DM intake was stimulated.…”
Section: Performancesupporting
confidence: 89%
“…Studies have been conducted for the feasibility of the use of cotton by-products in ruminant feeding, especially cottonseeds (Aferri, Leme, Silva, Putrino & Pereira, 2005;Stelzleni, Froetschel, & Pringle, 2013) cottonseed meal, (Pina et al, 2006) cottonseed hulls (Magalhães et al, 2005;Kazama et al, 2008) and cottonseed cake for dairy cows (Alves et al, 2010); and wheat offal and soybean meal to grasscutters (Wogar & Ayuk, 2012). However, differences in dry matter (DM) intake related to fat sources using cottonseed and its by-products were also observed (Cranston et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Valor de A superior aos encontrados neste trabalho foi relatado por Chizzotti et al (2005), que avaliaram a degradabilidade ruminal da silagem de capim-elefante e verificaram valor de 29,3% de fração A.…”
Section: Resultsunclassified
“…Apesar das variações nas frações A e B, as taxas de degradação da PB em %/hora (fração C) mantiveram-se constantes, entre 4 e 5%/hora, o que não ocorreu com a MS, cuja fração C variou de 6,7 a 12,8%/hora. Chizzotti et al (2005) avaliaram a degradabilidade ruminal da silagem de capim-elefante e observaram menor taxa de passagem da MS. Certamente, a pior qualidade do capim utilizado pelos autores, com mais de 10% de lignina, contribuiu para a menor fração c, pois, neste estudo, o capim-elefante ensilado apresentou apenas 3,30% de lignina.…”
Section: Resultsunclassified
“…A construção do modelo foi realizada utilizando-se um banco de dados constituído por médias de tratamentos obtidas em 12 experimentos com bovinos em crescimento e terminação (Carvalho et al, 1997;Ladeira et al, 1999;Cardoso et al, 2000;Dias et al, 2000;Tibo et al, 2000;Ítavo et al, 2002a;2002b;Rennó, 2003;Chizzotti et al, 2005) e 12 com vacas em lactação (Malafaia et al, 1996 a, b;Mora et al, 1996 a, b;Moreira et al, 2001;Oliveira et al, 2001;Silva et al, 2001;Assis et al, 2004a;Chizzotti, 2004;Magalhães et al, 2004a;Mendonça et al, 2004;Nörnberg et al, 2004;Soares et al, 2004).…”
Section: Methodsunclassified